Analysis of Vitamin A, C and Iron (Fe) Levels in Moringa Leaf-Based Pudding - Reski Zulhijjani; Nur Afni; Ayu Lestari (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2022)
Moringa Oleifera is a tropical plant that is easy to grow in trofical areas such as Indonesia. Moringa plant are shrubs with a height of 7-11 meters and thrive from lowlands to an altitude of 700m above sea level. Moringa plants can be used as a whole from the roots, leaves, fruit, flowers and seeds. The high nutritional value in moringa leaves can be used to meet the nutritional needs of nursing mothers and toddlers in their infancy. Moringa leaves contain high carbohydrates, protein, iron, calcium, vitamin C, Vitamin A, and potassium Moringa leaves can be consumed directly as a vegetable or as a food fortification. This research was conducted at the Chemistry Laboratory, Faculty Of Mathematics and natural sciences, Tadulako university. This type of research is a laboratory experimental using a completely randomized design (CRD) which is based on the analysis of levels of vitamins A C and iron (fe) in Moringa leaves pudding with 2 formulations. The results of the analysis of the laboratory tast of the content: analysis of levels of vitamin A vitamin C, iron (fe) with the Spectrophotometric Method. The results of the research show that moringa leaf pudding without sugar and using sugar obtained levels of vitamin A withour sugar (7,7890mg / 100g), levels of vitamin A using sugar (8,120mg / 100g), levels of vitamin C without sugar (26,827mg / 100g), levels of vitamin C using sugar (28,270mg / 100g) levels of iron (fe) without sugar (0.568mg / 100g), levels of iron (fe) use sugar (0.693mg / 100g). This research suggests that people can consume Moriga leaves/ Moriga Leaf pudding, because vitamin A, vitamin C and iron (fe) are quite high and good for health.